Improving a company’s commercial operations (on the example of the Logfort transport company) - D. V. Koplik (Publishing House of the State University of Management, 2021)
The commercial activities of the Logfort transport company have been analysed through a functional-environment analysis. Commercial weaknesses of the Logfort transport company have been identified and measures for its improvement have been proposed. The topic of the paper is relevant because the current crisis and the increasing competition almost every year make it necessary to improve various aspects of the company every year. The theoretical aspects of functional-environmental analysis have been presented in order to apply them to the object of study. The theory regarding both company’s the external and internal environment has been studied. An analysis of the object of study for each item of the functional-environmental analysis has been presented. As a result of the work, the problems of the Logfort company, which are typical for many small firms, have been generalised. The proposed recommendations will be suitable for the majority of small companies to address the problems identified. The paper uses the method of generalisation, synthesis and description.